Benefits of Cloud Computing: An Assessment of Its Implications in Nigerian Industries (International Journal of Engineering and Computer Science, 2015)
Cloud Computing provides the means through which everything from computing power to computing infrastructure, applications to personal collaboration can be delivered to you as a service whenever you need. This study was motivated by the fact that most Nigerian industries have experienced unexpected loss of files from their system units hence virus infection and/or some other sudden crash of the Hard disks. The study therefore seeks access cloud computing, its benefit to business organizations and implementation to Nigerian industries. The opinions of 500 respondents working in some industries in the South Eastern Nigeria were sampled through questionnaires statistically analyzed using the weighted mean average method. The result shows that the benefits of Cloud Computing package, provision of up-scaling opportunities and shared service, as well as easier allocation of resources to a diversity of users. However, these benefits were found to come with some socioeconomic and business implication.